GLOBE US Leadership Preferences versus Black American Catholics’ GLOBE Leadership Preferences - McNeely, James P. (The international journal of religion and spirituality in society, 2017)
Although numerous studies focusing on leadership preferences and differences have been completed over the last ten years, this is the first study to examine Black American Catholics’ (BAC) leadership preferences and provide findings that may be used by the Roman Catholic Church. The purpose of this study was to determine the differences between normative Global Leadership and Organizational Behavior Effectiveness (GLOBE) US leadership preferences and Black American Catholics’ GLOBE leadership preferences, including differences based on demographics. Participants were anonymously surveyed and data were collected; significant leadership behavior characteristics were identified and documented. Statistical analyses included significant differences found between age, years of work experience, formal education, and charismatic/value-based leadership. There were also significant differences found between age, formal education, and team-oriented leadership. Additionally, a comparison of differences between Black American Catholics’ (BACs) mean preferences and GLOBE US normative leadership preferences found differences in four of the six GLOBE leadership behaviors. The identification of these characteristics could allow for better identification, selection, recruitment, and retention of future leaders for local, regional, national, and international interests.